Perlindungan Hukum terhadap Anak di Bawah Umur sebagai Pengemis - I Wayan Edy Darmayasa; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2020)
Children are not objects of deviant behavior or inhuman actions by anyone. However, in reality the child exploitation in Indonesia has become a complex problem. This research was conducted with the aim of describing the legal arrangements for children as beggars and the legal protection for minors as beggars. This study used a normative legal research method as well as statutory and conceptual approaches. The results of this study indicated that the regulation of minors as beggars is contained in Article 2 paragraph 1 of the Child Welfare Law No. 4 of 1979 which explains that the right to care for welfare care and guidance with affection is the right of the child as well as the care for the development of children in a healthy and good family. In addition, legal protection for minors as beggars as stipulated in the Child Protection Law No. 35 of 2014 in conjunction with Law No. 23 of 2002 can be in the form of socio-economic health services and adequate education.